Literature Review: Efektivitas Kurikulum Merdeka Dalam Meningkatkan Kemandirian Belajar Peserta Didik - Lubis, Adelia Marta; Sinaga, Erickson; Simbolon, Legi Likasri; Aulia, Nazwa; Munthe, Raja Parnaungan (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
The Independent Curriculum is an educational policy designed to provide learning flexibility, differentiation, and student-centered learning experiences. However, its effectiveness in fostering independent learning still shows mixed results across educational units. This study aims to analyze the effectiveness of the Independent Curriculum in enhancing student learning independence through a literature review approach. Data were collected from scientific articles indexed by Google Scholar, DOAJ, and the Garuda Portal with keywords related to "Independent Curriculum," "independent learning," "student autonomy," and "self-regulated learning." The analysis process was carried out through the stages of identification, filtering, and data extraction to identify patterns of findings, supporting factors, and barriers to implementation. The results of the study indicate that the flexibility of the curriculum structure, differentiated learning, and the Pancasila Student Profile Strengthening Project activities consistently contribute to improving students' abilities to plan, manage, and evaluate their learning process independently. However, the effectiveness of the Independent Curriculum is strongly influenced by teacher readiness, school facilities, learning culture, and students' internal motivation. Schools with strong learning ecosystems demonstrate significantly greater development of independence than educational units with limited resources. Overall, the Independent Curriculum has significant potential to foster independent learning, but its success requires synergy between policy, teacher competency, and a supportive learning environment.